2011
DOI: 10.5301/jva.2011.8309
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Central Venous Cannulation in Infants Weighing Less than 5 Kilograms

Abstract: Our experience suggests that ultrasound-guided central vein cannulation can be performed by well-trained physicians in infants weighing less than 5 kg without relevant risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
2
17
1
4
Order By: Relevance
“…Another meta-analysis of randomized and non-randomized trials showed improved technical success with US guided cannulation although the authors reported a high risk of bias in most of the studies included. (7) Non-comparative studies have shown a technical success rate near 100% in US guided IJV cannulation in children (16)(17)(18)(19). The success rate of US guided IJV cannulation in our study was 83% which is lower than the aforementioned studies.…”
contrasting
confidence: 80%
“…Another meta-analysis of randomized and non-randomized trials showed improved technical success with US guided cannulation although the authors reported a high risk of bias in most of the studies included. (7) Non-comparative studies have shown a technical success rate near 100% in US guided IJV cannulation in children (16)(17)(18)(19). The success rate of US guided IJV cannulation in our study was 83% which is lower than the aforementioned studies.…”
contrasting
confidence: 80%
“…The authors described a head‐neck position similar to ours, but they evaluated the IJV at the level of the cricoid cartilage. In a similar study by Di Nardo et al 9 the RIJV was found to be anterolateral with respect to the CA in 66% and lateral in 28% of patients weighing <5 kg 9 . The authors did not mention the head‐neck position of the infants, but only reported that they applied the 30° Trendelenburg position in some patients.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, blood aspiration was performed mostly by withdrawing the needle or angiocath, and sometimes, the posterior wall of the IJV was punctured using the transfixation technique. 11,12 Although puncturing the posterior wall of the IJV carries the risk of accidental puncture of the artery, there were no cases of arterial puncture in either group.…”
Section: Discussionmentioning
confidence: 95%